KAJIAN BENTUK DAN SIMBOL KUJANG SUNDA - Hendri Saifulhayat (ARTic, 2018)
Kujang is known and considered as a weapon tradition that represents Sundanese society culture. Looking back, that a knife is the development of a sharp-sided discovery made up of rocky chunks of kalcedon that make humans rank first in the food chain on the face of the earth. The knife transforms into a long sword, thrown into a spear, jagged into a saw, squeezed with axis into scissors and many other more specific functions into a variety of tools because of the growing demands of life needs. Kujang comes from Kudi Hyang. Kudi is functionally a farming tool that is prepared to honor and worship Hyang, the supreme ruler of the universe. The concept of Kujang is far from the utility function of a tool or a weapon. Kujang is a symbolic artifact that functions intrinsically, and not a weapon, because planning from the beginning can be distinguished by making weapons. Then Kujang in form follows function proven not to fulfill utility requirement. Kujang which is identified with the term "nyumput buni dinu caang" or hidden in a visible / bright place, can be fully revealed through a scalpel of Sundanese cultural teaching that is Panca Niti or five stages of understanding. This teaches us to understand something more deeply, from the meaning, meaning, nature, divinity and understanding in a comprehensive way. Kujang is loaded with full of spectacle, guidance, teaching or education to the state, and the potential will be revealed more positive things behind its appearance.